Effectiveness of interventions on healthcare professionals' understanding and use of conscience: a systematic review protocol. Issue 7 (27th July 2022) - Lamb, Christina; Kennedy, Megan; Clark, Alex; Pituskin, Edith; Kirkwood, Ken; Babenko-Mould, Yolanda
Abstract : Introduction: Conscience is central to moral decision making. In the context of morally pluralistic workplaces today, healthcare professionals' conscience may prompt them to make moral decisions to refrain from providing services they morally disagree with. However, such decisions are largely viewed as contentious, giving rise to polarising arguments for and against healthcare professionals' freedom of conscience. Yet, little work has been done to understand and support healthcare professionals' conscience. Instead, the rising polarity related to healthcare professionals' freedom of conscience stems from a central lack of understanding of what conscience is and the relevance it holds for healthcare professionals' clinical practice. Therefore, the degree and extent to which healthcare professionals are supported to understand and use their conscience is unknown. The objective of this review is to critically analyse the scholarly evidence available to ascertain the effectiveness of interventions that support healthcare professionals to understand and use their conscience in care practice. Methods and analyses: At least two reviewers will systematically review 10 interdisciplinary, scholarly databases to examine qualitative, quantitative and mixed-methods studies including clinical trials pertaining to interventions related to conscience for healthcare professionals. Databases to be searched include: the Cochrane Controlled Register of Trials, Medline, EMBASE, PsycINFO, Cumulative Index for Nursing and Allied Health Literature (CINAHL), Academic Search Complete, ATLA Religion Database, Religion and Philosophy Collection, PhilPapers and Scopus. Databases were searched in May 2021. Study screening, selection, extraction and risk of bias assessments on each study using the Mixed Methods Appraisal Tool will be independently conducted by independent reviewers. Descriptive data synthesis will be carried out. Statistical analysis and meta-analysis will be conducted as relevant, based on homogeneity of findings. The quality of the aggregate evidence will be assessed using the Grading of Recommendations, Assessment, Development and Evaluations criteria. Ethics and dissemination: Ethical approval is not required for this review. This protocol will not involve individual patient information endangering participant rights. The results will be reported in a peer-reviewed journal and disseminated at conferences. PROSPERO registration number: CRD42021256943.